PROBIOTICS FOR PREVENTION OF NECROTIZING ENTEROCOLITIS : A COMPREHENSIVE SYSTEMATIC REVIEW - Aisyah Sabrina, Syarifah Tiara; Melinda, Eza; Jalaluddin Machalli, Muchammad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Necrotizing enterocolitis (NEC) is the most common serious acquired disease of the gastrointestinal tract in preterm infants. It is characterized by bowel wall necrosis, of various length and depth. Bowel perforation occurs in one third of the affected infants. Although 5 to 25 of cases occur in term infants, it is primarily a disease of preterm infants with the majority of cases occurring in very low birth weight infants (infants with birth weight 1500 g). The aim: This study aims to show about probiotics for prevention of nercrotizing enterocolitis. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 26 articles, whereas the results of our search on SagePub brought up 48 articles, on Google Scholar 5660 articles. The results of the search conducted for the last year of 2014 yielded a total 15 articles for PubMed, 35 articles for SagePub, and 4567 articles for Google Scholar. The result from title screening, a total 11 articles for PubMed, 16 articles for SagePub, and 8 for Google Scholar. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: The risk-benefit ratio depends on the incidence of NEC in a neonatal intensive care unit, and evidence has shown that preventive measures probiotic administration can result in a decrease in NEC.